PENGARUH FAKTOR LINGKUNGAN, PSIKOLOGIS DAN INDIVIDU TERHADAP KEPUTUSAN PEMBELIAN PERHIASAN EMAS DI KOTA BANJARMASIN - Dyah Sri Wulandari; Nuril Huda; Siti Aliyati Albushairi (Universitas Lambung Mangkurat, 2017)
Gold jewelry is the type of products that are most frequently encountered in everyday life, many things that make someone decide to buy gold jewelry, this study aimed to analyze the factors that influence purchasing decisions gold jewelery, where environmental factors, psychological and individuals in hypothesize influence the purchasing decisions of gold jewelry. The population used is the buyers of gold jewelry in the city of Banjarmasin, 220 respondents drawn using purposive sampling technique. The analysis used in this study is the examination of the structural equation model to test the hypothesis by using Structural Equation Model (SEM) with statistical analysis tools AMOS 18. These results indicate that environmental factors have a significant effect on purchasing decisions, psychological factors significantly influence purchasing decisions and the individual factors also significantly influence the purchasing decisions of gold jewelry in the city of Banjarmasin. Based on this research, the advice of research that can be done is that marketers can consider psychological factors as a marketing strategy, especially in Banjarmasin. Based on the research development agenda of future research should examine other variables that have not been studied and is also directed at the sample and area larger studies eg all South Kalimantan region or on different objects such as agate, diamonds or other.